Optimal Form for Compliance of Membrane Boundary Shift in Nonlinear Case - Y. Yousfi; I. Hadi; A. Benbrik (International Journal of Mathematics and Mathematical Sciences)
In this work, we search the existence shifting compliance optimal form of some boundary membrane, which is not elastic and not isotropic, generating nonlinear PDE. An optimal form of the elastic membrane described by the p-Laplacian is investigated. The boundary perturbation method due to Hadamard is applied in Sobolev spaces.